Activation of myenteric glia during acute inflammation in vitro and in vivo - Rosenbaum, Corinna; Schick, Martin; Wollborn, Jakob; Heider, Andreas; Scholz, Claus Jürgen; Cecil, Alexander; Niesler, Beate; Hirrlinger, Johannes; Walles, Heike; Metzger, Marco (PLOS ONE, 2016)
Enteric glial cells (EGCs) are the main constituent of the enteric nervous system and share similarities with astrocytes from the central nervous system including their reactivity to an inflammatory microenvironment. Previous studies on EGC pathophysiology have specifically focused on mucosal glia activation and its contribution to mucosal inflammatory processes observed in the gut of inflammatory bowel disease (IBD) patients. In contrast knowledge is scarce on intestinal inflammation not locally restricted to the mucosa but systemically affecting the intestine and its effect on the overall EGC network.
Gesehen am 05.05.2020